Transport phenomena and KSS bound in quantum-corrected AdS black holes - Pourhassan, Behnam; Sakalli, Izzet (Springer, 2025)
In this paper, we study quantum effects on transport properties of charged anti-de Sitter (AdS) black holes, focusing on non-perturbative corrections to the shear viscosity-to-entropy ratio. We consider exponential corrections to both the entropy and transport coefficients, examining their impact on the Kovtun-Son-Starinets (KSS) bound. Through detailed analysis, we demonstrate that quantum corrections significantly modify transport phenomena, particularly in the small-horizon-radius regime. We explore three scenarios: unmodified shear viscosity with quantum-corrected entropy, quantum corrections to both quantities, and preservation of the universal ratio. Our results show that electrical conductivity, bulk viscosity, and thermal conductivity receive substantial modifications from quantum effects while maintaining consistency with established transport laws. The analysis reveals that for the positive correction coefficient, the KSS bound can be violated, while for the negative correction coefficient, it remains valid. We demonstrate these effects through numerical analysis and graphical representations, providing insight into quantum transport phenomena in strongly coupled systems.
Keywords: Field-Theories; Entropy; Viscosity; Gravity; Qcd